1994
DOI: 10.1203/00006450-199407001-00021
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Necrotizing Enterocolitis May Be Dependent on Patterns of Bacterial Adherence and Intestinal Colonization: Studies in Caco-2 Tissue Culture and Weanling Rabbit Models

Abstract: [J. G. M.]Necrotizing enterocolitis (NEC) is one of the leading causes of death in neonatal intensive care units. The underlying pathophysiology of NEC is poorly defined, although there is a suggestion that bacterial agents play an important role in the process. In this study, we evaluated bacterial isolates from 17 NEC cases and matched asymptomatic control infants. Isolates from NEC patients were no more likely than control isolates to be adherent to enterocytes, as assessed by a Caco-2 cell tissue culture m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…In a subsequent series of studies23 using the microbial isolates from our prospective epidemiological study6 we showed that coinfection with specific Gram positive bacterial species (obtained from infants without NEC) blocked adherence of Gram negative organisms in a Caco-2 cell system and blocked E coli induced gut mucosal injury in a weanling rabbit ileal loop model. We also recently reported that non-toxigenic E coli strains can translocate enterocyte monolayers, a phenomenon that can also be blocked by the aforementioned specific Gram positive bacteria isolated from healthy infants 24.…”
Section: Discussionmentioning
confidence: 93%
“…In a subsequent series of studies23 using the microbial isolates from our prospective epidemiological study6 we showed that coinfection with specific Gram positive bacterial species (obtained from infants without NEC) blocked adherence of Gram negative organisms in a Caco-2 cell system and blocked E coli induced gut mucosal injury in a weanling rabbit ileal loop model. We also recently reported that non-toxigenic E coli strains can translocate enterocyte monolayers, a phenomenon that can also be blocked by the aforementioned specific Gram positive bacteria isolated from healthy infants 24.…”
Section: Discussionmentioning
confidence: 93%
“…We opted against the use of live infectious agents such as Enterobacter sakazakii (17) because the dose of the inciting agent (density of Enterobacter population in the gut lumen) is difficult to control and normalize by body weight/size of the animal. We also evaluated models of NEC-like injury in experimental animals such as rabbits (37), quails (5), and piglets (42) but did not find a suitable way to induce comparable mucosal injury in adult animals. TNBS-mediated mucosal injury was particularly suitable for agebased comparisons because TNBS colitis in adult mice is associated with a striking increase in the number of T-lymphocytes with relatively few macrophages (7,15,35,36,44), which contrasted with the leukocyte infiltrates we observed in NEC.…”
Section: Tnbs-induced Gut Mucosal Injury In Pups Is Associated With Imentioning
confidence: 99%
“…Probiotics tend to enhance the intestinal mucosal protective barrier (17), and several clinical trials have shown a decrease in the incidence of NEC with their administration (18,19). Furthermore, studies have shown that probiotics aid in promoting a T H 1 immune response by upregulating IgA and downregulating IgE (20).…”
Section: Cytokinesmentioning
confidence: 99%